Hemodynamic effects of combined sildenafil and L-arginine during acute pulmonary embolism-induced pulmonary hypertension - Souza-Silva, A. R.; Dias-Junior, C. A.; Uzuelli, J. A.; Moreno, H.; Evora, P. R.; Tanus-Santos, J. E. (Elsevier B.V., 2005)
Sildenafil attenuates acute pulmonary embolism-induced pulmonary hypertension. However, the hemodynamic effects of sildenafil in combination with other vasodilators during acute pulmonary embolism have not been examined yet. In the present study, we examined the hemodynamic effects of combined sildenafil (0.25 mg/kg, i.v.) and L-arginine (100, 200, 500, and 1000 mg/kg/h, i.v.) in an anesthetized dog model of acute pulmonary embolism. Plasma nitrite/nitrate (NOx) and cGMP concentrations were determined using an ozone-based chemiluminescence assay and a commercial enzyme immunoassay, respectively. We found that L-arginine alone did not attenuate acute pulmonary embolism-induced pulmonary hypertension. However, significant decreases in mean pulmonary artery pressure were observed 30, 45, 60, and 75 min after the administration of sildenafil alone or after the combined administration of sildenafil and L-arginine (all P<0.05). No significant differences among groups were observed in the respiratory parameters. While L-arginine significantly increased NOx concentrations, cGMP concentrations increased only when sildenafil was administered (all P<0.05). These results suggest that while sildenafil attenuates acute pulmonary embolism-induced pulmonary hypertension, L-arginine does not enhance the beneficial hemodynamic effects of sildenafil. In addition, these findings suggest that stimulation of NO synthesis with L-arginine during acute pulmonary embolism does not produce beneficial effects. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: acute pulmonary embolism; L-arginine; nitric oxide; phosphodiesterase-5 inhibitor; pulmonary hypertension; sildenafil